LEGAL CULTURE MASYARAKAT OPTIMIS DAN TAAT HUKUM SEBAGAI UNSUR PENTING DALAM PERANAN HUKUM UNTUK PEMBANGUNAN EKONOMI (Lex Jurnalica, 2019)
AbstractThe economic condition of a state is very important for the nation and state. Legal experts economic mention that conditions are associated with law system in the nation and state itself. This can be true but it is not absolute. In Indonesia, there are already many laws and regulations in many fields. The regulations have also been very good in its contents but in practice it still does not apply effectively. An optimistic attitude is needed in the law to be able to support economic development. An optimistic attitude towards the legal order at all levels of regulations will provide convenience for achieving better economic development. So the next question, is the legal culture of the people ready to support the legal order? For the purpose of achieving economic development. Looking at recent events, I am hesitant about this. The writer sees that too many things are at the center of the public's attention, but these things will not bring economic development to the nation and state. In the law to eradicate corruption, there are even more state officials, more specifically to regional heads who commit criminal offense of corruption. Regarding finance technology, it has been widely circulating in the community but it has become a problem. This is because the cause of speed and responsiveness of law makers is less rapid than the needs of the people. Losing speed is not only because of technical matters but because of ignorance from the law makers themselves. As a result, after a lot of problems in the people that be stated in media regarding finance technology, the regulations (legal basis) were hurriedly made. Something done in a hurry will not give maximum result. Similar to the rushed regulations (legal basis) for finance technology, it will not provide maximum results for the community. So it should be the character of members of the House of Representatives as legislators to respond quickly and properly to make Acts regarding finance technology. This is really embarrassing, because in this very hour, the United States has been able to send the second robot on Mars planet, but we are still struggling with things that will not provide any benefit to our nation and state? So the question of the author is